Konsep Manusia (Al-Insan) Dalam Al-Qur’an Sebagai Khalifatullah Dengan Perspektif Kepribadian Sigmund Freud - Rohmatin, Ilma Nur; Soleh, Achmad Khudori (Publikasi Indonesia, 2025)
Humans are an important object of study to be studied, where humans have various traits and personalities. In this case, human beings become objects as caliphs who will convey scientific and spiritual knowledge to other humans. The purpose of this study is to correlate the teachings in the Qur'an with psychological science, especially in terms of human personality. The methods used are the literature study method and maudhu'i. The results of this research are (1) Al-Insan is positioned as a khalifatullah who will spread knowledge, spirituality and intellectual. (2) As a khalifatullah, human attitudes can be connected with Fredu's personality theory, namely that there is an Id that comes from the desire or desire of humans to do something. The ego that will make man realize his desires with a good or bad response as a leader in making Superego decisions that come from his morality habits, which will shape his ego.